Pilot plant for sequential processes in the remediation of industrial effluents - Lovera, Daniel (2000)
In recent years, technologies are being developed to treat acid mine drainage ( AMD ) , rock drainage (ARD ) and other effluents which are causing environmental pollution, both in water and soil . International environmental regulations today are quite demanding , since the current priority is the preservation of the environment. Currently has been developing terminology SBR secuential batch reactor describing a group of variable volume systems for activated sludge treatment , where the processes of sedimentation, aeration and clarification are performed in the same reactor. In the SBR happen sequentially in time different processes of equalization, aeration and clarification. This added to the biomass technology allows treatment of a wide range of metallic and organic compounds. SBR is successfully applied in USA and Canada hundreds of industrial plants. In this context we construct the pilot effluent treatments , incorporating modern technologies for the remediation of effluents from metallurgical plants , for it had to resort to the techniques of plant design plant, and we used software design teams and prototypes; as well as environmental considerations of clean technologies.